Evaluation of headphone phase equalization on sound reproduction. (15th December 2019) - Li, Guangju; Zheng, Chengshi; Li, Xiaodong; Yu, Teng; Bleeck, Stefan; Sang, Jinqiu
Highlights: We develop a headphone equalization method to generate a linear phase response and keep original magnitude response. We compare the phase equalization method with other equalization methods through objective and subjective tests. The linearity of phase response is important for the decay speed of the corresponding transient response. The phase equalization method improves headphone reproduction in sound clarity significantly. Abstract: Headphone equalization can help to deliver high perceptual sound quality. The headphone-to-eardrum transfer function (HETF) equalization can be used to control magnitude and phase responses of headphones. Magnitude equalization is still elusive on how to set a preferred target response while phase equalization is an important but overlooked method. Here the targets of magnitude equalization and phase equalization on headphone reproduction were evaluated through objective and subjective experiments. The objective evaluation shows that the linearity of phase response is important for the decay speed of the corresponding transient response. The subjective experiments show that the target of a linear phase response, but not a flat magnitude response, is able to significantly improve headphone reproduction quality in sound clarity.